การให้ความรู้โดยเภสัชกรต่อความร่วมมือในการใช้ยาต้านไวรัสเอดส์ ณ โรงพยาบาลวชิระภูเก็ต - ศุทธินี ตันพงศ์เจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
A prospective one-group repeated-measures study was conducted in HIV-infected adult patients at Vachiraphuket hospital to evaluate the effect of an educational and counselling intervention on the adherence to antiretroviral therapy, patients knowledge and quality of life. Fifty patients were enrolled in this study between December 2003 and March 2004. There were estimately equal number of female and male subjects with an average age of 35.08+-6.72 years and most of them have acquired HIV through sexual contact. Before treatment, ninety percent were classified as group C3 and B3 according to US Centers of Disease Control and Prevention (CDC) and the mean baseline CD[subscript 4] cell count was 83.86+-63.69 cells/microlitre. Seventy percent of the subjects had opportunistic infections. The most common one were candidiasis, pneumocystis carinii pneumonia and tuberculosis, resectively. During this study, the mean CD[subscript 4] cell count increased from baseline to 318.87+-219.95 cells/microlitre and only 8% of participants still had opportunistic infections. All subjects received GPO-Vir(R), HARRT regiment, which included stavudine (d4T), lamivudine (3TC) and nevirapine. The average length of treatment was 9.34+-6.64 months. Besides antiretroviral agents, patients also received vitamin and other medications such as cotrimoxazole or fluconazole for preventing opportunistic infections. Most subjects recieved 5.34+-1.84 tablets per day from 3.93+-1.68 drug regimens and the frequency for taking these medications was twice a day. After completing two educational interventions, each intervention was about 29 days apart, the knowledge score regarding the disease and medications tended to increase significantly at the first time (E1) and the second time (E2) of educational intervention compared to the baseline (p<0.05). However, no significant effect on quality of life was observed over three-month period. A statistically significant increase in adherence was observed between baseline-E2 (p<0.05). Even though the increase in adherence between baseline- E1 and E1-E2 was not statistically significant, however, most of subjects changed their adherence to positive aspect. Using multivariate logistic regression analysis, there was a significant correlation of adherence included the mental quality of life score (OR = 1.1) and previous adherence status (OR = 27). The result showed that major reasons for nonadherence were forgetfulness or busy and being away from home. Adherence and clinical outcome were significantly associate (OR = 8.3, p = 0.001).